ANALISIS STUDI KELAYAKAN USAHA BUDIDAYA IKAN NILA DI DESA SIGERONGAN KECAMATAN LINGSARKABUPATEN LOMBOK BARAT - IDA AYU KETUT MARINI; IDA BAGUS EKA ARTIKA (Universitas Mahasaraswati Mataram, 2018)
Tilapia is a freshwater fish, not only how to maintain it more easily than other freshwater fish, but also more resistant to disease and has a high tolerance for water salinity levels, so it can also be cultivated in ponds with brackish water. In addition, tilapia is widely chosen by the community to be cultivated because of its ease of marketing, and favored by many people.This study is a case study research, with the aim to determine the feasibility of the investment plan in tilapia aquaculture in cages in Sigerongan Village, Lingsar District, West Lombok Regency. The research was conducted at UD. MAHNEP, using investment criteria methods namely Revenue Cost Ratio (R / C) and Break Event Point (BEP). The results show that the value of the Revenue Cost Ratio (R / C) is 1.5 which means that the amount of revenue that will be obtained from the tilapia enlargement business is 1.5 times the amount of operational costs incurred. The value of Break Event Point (BEP) is 1,947.8 kg, which means that the tilapia enlargement business breaks even when the production in one production process is 1,947.8 kg.From the results of the study it is suggested, if the cultivator wants the amount of revenue higher than 1.5 times the production cost, the number of seeds should be increased, while the number and size of the pond should not be increased